—-RETRACTED—- THREE YEARS ANALYSIS OF POISONING CASES OF FORENSIC MEDICINE TOXICOLOGICAL LABORATORY, KHYBER MEDICAL COLLEGE, PESHAWAR: RETRACTED (The article has been retracted due to Data Property Issue) - Shazia, Salma; Wazir, Abdul Haq; Rashid, Haroon ur; Khalil, Zahid Hussain (Journal of Ayub Medical College Abbottabad, 2020)
——–RETRACTED—– Background: Poison is defined as any substance which harms, endangers or even kills a person irrespective of the quality or quantity. Pakistan is a developing country and farming is the major occupation of the majority of the population. Due to the easy availability and increased use of pesticides, the accidental and suicidal poisoning is very common. The objective of the study is to find out the most common poison used by the people in the general population and its frequency in our setup. Methods: The present cross-sectional study with retrospective data collection was undertaken in the Department of Forensic Medicine, Khyber Medical College (KMC) Peshawar to determine the frequency of different poisons detected in various samples brought to the toxicological laboratory. A three-year data (1stJanuary 2014 to 31 December 2016) was retrieved from Forensic Laboratory of KMC, Peshawar. Different methods were used for the detection of poisons. All the cases coming from Khyber Pakhtunkhwa province were included whereas; cases from other provinces were excluded. Results: The study revealed that poisoning was more common among females and the most common age group affected was 21-25 years. The incidence of positive cases was more in Peshawar district followed by Swat district. The common poison detected was phosphine (wheat pill). Conclusion: Female and young people from Peshawar and Swat are more prone to Aluminum Phosphide (wheat pill) poison. It is a dangerous and lethal poison, so healthcare workers at emergency department ought to be prepared for such cases. Furthermore, its routine use as a domestic pesticide has to be strictly prohibited by creating awareness among the public. Keywords: Aluminum Phosphate; Poisoning; Phosphine; Wheat pill; Homicide; Suicide